Prevalence and Risk Factors Predicting Onychomycosis in Patients with and Without Diabetes Mellitus in Spain: A Cross-Sectional Study - David Navarro-Pérez; José Luis Lázaro-Martínez; Sara García-Oreja; Teresa Pérez-Pérez; Francisco Javier Álvaro-Afonso; Aroa Tardáguila-García (Journal of Fungi)
Background: A cross-sectional study was conducted to investigate the prevalence of onychomycosis (ONM) and its causative pathogens in populations with and without diabetes in Spain. The association between the presence of ONM, different risk factors, and comorbidities was also examined. Methodology: A total of 160 patients with diabetes and 160 individuals without diabetes were recruited consecutively. A single investigator recorded the relative data of each patient and sampled nail dust and detritus for microbiological culture and polymerase chain reaction (PCR) analyses of patients who showed clinical signs of fungal infection. Results: The prevalence of ONM was 36.88% (59/160) in the population with diabetes, 17.5% (28/160) in the population without diabetes, and 34.35% (45/131) in the population with diabetic foot. Dermatophyte fungi were most frequently identified, although the proportion was higher among those without diabetes than those with diabetes (19/28 and 28/59, respectively). However, the rate of mixed infections was higher in the population with diabetes compared to those without diabetes (13/59 and 2/28, respectively). A statistically significant association was found between the presence of diabetes and the risk of ONM (p < 0.001; odds ratio (OR) = 2.754; 95% confidence interval (CI) 1.652–4.679). The risk factors associated with ONM among the patients with diabetes were a history of minor amputation, revascularisation, or cardiovascular disease, a low educational level, HbA1c values > 7%, hyperkeratosis, and subungual detritus. Among the patients without diabetes, nail thickening and chromonychia were associated with ONM. Conclusion: The results of this study suggest that the early diagnosis of ONM and knowledge of risk factors among patients with diabetes could enable the prevention of ONM, complications, and serious injuries through education for professionals and patients.